Geology of the Ionian Basin and Margins: A Key to the East Mediterranean Geodynamics. Issue 8 (5th August 2019) - Tugend, J.; Chamot‐Rooke, N.; Arsenikos, S.; Blanpied, C.; Frizon de Lamotte, D.
Abstract: We revisit the nature, structure, and evolution of the Ionian Basin and its surrounding passive margins (Apulia, Eastern Sicily/Malta, and Cyrenaica margins). Relying on geological observations (wells, dredges, and dives) and seismic calibrations from the surrounding platforms and escarpments, we present age correlations for the deepest sedimentary sequences of the Ionian Basin. Two‐ship deep refraction seismic data combined with reprocessed reflection seismic data enable us to identify, characterize, and map these thick sedimentary sequences and to present a consistent seismic stratigraphy across the basin. At a larger scale, we present new geological transects illustrating the tectonostratigraphic relationships between the Ionian Basin and its surrounding rifted margins. On this basis, we suggest that a Late Triassic‐Early Jurassic rifting preceded the late Early Jurassic to Middle Jurassic formation of the Ionian Basin. The combination of geophysical and geological arguments suggests that the entire deep basin is floored with oceanic crust of normal thickness, but with high seismic velocity in the upper part. Upscaling our results in the framework of the eastern Mediterranean, we propose that the Ionian Basin represents the remnant of a short‐lived oceanic basin resulting from the interaction between two propagating oceans: the Central Atlantic and the Neo‐Tethys. Key Points: We propose a coherent stratigraphic framework for the margins of the Ionian Basin using seismic data (Apulia, Malta, Sirte, and Cyrenaica) The age of the Ionian Basin is reevaluated to the Early‐Middle Jurassic interval, following a Triassic‐Lower Jurassic episode of rifting The Ionian Basin is a short‐lived remnant resulting from the interaction between two propagating oceans, Central Atlantic and Neo‐Tethys